ANALISIS TEKNIK DASAR PASSING DAN CONTROL PADA PERTANDINGAN LIGA FUTSAL PROFESIONAL PUTRA 2021/2022 - Taufik Perdiana, Mohamad; Ramadhan, Chairul Umam; Bakhri, Rafdlal Saeful (Jurnal Arena Olahraga Silampari, 2023)
The purpose of this study is to determine the basic passing and control technique activities in the Bintang Timur Surabaya team of the 2021/2022 professional futsal league and the dominant passing and control techniques carried out by the Bintang Timur Surabaya team. The method used by researchers is a descriptive quantitative method. The source of the data taken was by watching the rematch of the Bintang Timur Surabaya team in the second round. The results of the analysis of the basic passing and control techniques of the Bintang Timur Surabaya team, the total passing carried out by the Bintang Timur Surabaya team was 4,246 times with a description of passing success 3,945 times (93%), and a total control of 3,546 times with a description of control success of 3,402 (96%) and control errors 144 (4%). With the average basic passing and control techniques in 11 matches during the second round are 386 passing techniques in each game and the average control performed in each game is 322. As for the dominant passing and control techniques carried out are the passing inside foot pass technique, and direct control control techniques. Keywords: Futsal, Basic technique, Passing, Control, Bintang Timur Surabaya